ABUNDANCE OF YELLOW ALKALOID ‘BERBERINE’ IN THE MEDICINAL PLANT OF TALI KUNING (Tinospora dissitiflora Diels.) COLLECTED FROM MANOKWARI – WEST PAPUA - Wahyudi (JURNAL KEHUTANAN PAPUASIA, 2019)
This research was conducting to quantify the berberine concentration. Rapid method using 1H-NMR was used to determine berberine quantitative and qualitatively from the crude extract. Tali kuning was collected from Manokwari Papua Barat and powdered with hammer mill. Sonication was employed to extract using methanol at room temperature. 500 µg authentic berberine chloride were dissolved in 5.4 mL methanol-d4 (containing 84.4 µg anthracene). 1H-NMR spectra were recorded in methanol-d4 (99,9%) using JEOL JNM-ECX 500. Each sample was scanned for 100 using the following parameter 0.18 Hz/point, spectral width 14400 Hz, pulse with 4.0 US, relaxation delay 2 sc. Peak areas were used for qualitative analysis and integration of each peach were employed for quantitative analysis. The results demonstrated that 1H-NMR signal pattern of H-13 and H-8 recorded from Tali Kuning, and Amur corktree were well recorded, and in accordance to the berberine chloride standard. Using peak integration of H-13 and H-8, the berberine quantity in Tali kuning is 18.06 mg/g of dried powder, and 22.78 mg//gr for Amur corktree. Berberine percentage based on the weight of oven-dried-extracts was 8.34% (MC 7.54%) and 12.04% (11,54%) for Amur corktree and Tali kuning.